Analisis Gaya Belajar pada Anak Disleksia di Sekolah - Aqobah, Siti Jumrotul; Fauzi Fadliansyah; Uvia Nursehah (Arus Jurnal Pendidikan, 2025)
This study aims to analyze the learning styles of dyslexic children. The background of the study is the lack of understanding regarding effective learning styles for dyslexic students. Dyslexia is not a sign of low intelligence but rather a difference in how the brain processes written information. This research used a qualitative case study approach. The subjects were two 5th grade students who showed characteristics of dyslexia. Data collection techniques included observation, interviews with teachers and parents, and documentation. The results showed that dyslexic students tend to have kinesthetic and visual learning styles, with main challenges in reading and interpreting letters. It is concluded that tailoring learning approaches based on their dominant learning styles can improve the learning outcomes of dyslexic students